Back from the future eaudiobook A celebration of the greatest time travel story ever told. - Gilmore, Brad (Tantor Media, 2020)
The history of the films, cartoons, toys, and more: The Back to the Future series is a timeless collection that is greatly revered by all audiences. The beauty of this book by Brad Gilmore is that it doesn't present the history of the film as textbook information. Gilmore discusses these films from a place of passion and so effectively reveals how the history behind the movies is just as engaging as the films themselves. From a fan, for the fans: There's a host of information out there on the Back to the Future trilogy, but never before has there been a book like this. Gilmore, a radio and television host, also happens to be a die-hard fan of the movies. As a fan speaking to fellow fans, Gilmore dives into fan theories and provides the answers to all the questions listeners could possibly have—because they are the very questions he himself has asked. Unheard details and trivia: Not only is Gilmore a diehard fan, but he is also an expert on all things Back to the Future , a fact made evident by the podcast he hosts, Back to the Future: The Podcast . Pairing his knowledge with his passion for the films, Gilmore uses this book to discuss details and movie trivia that reveal just why these movies have stood the test of time.